Leśniewskian Ontology with Many-argument Predication - Paśniczek, Jacek (History and philosophy of logic, 2023)
Leśniewskian Ontology (LO) is a system in which the basic subject-predicate formula takes the form of a b and express one-argument predication, e.g. John is a student. In LO's language, there is no many-argument form of predication given that would allow for the structural expression of, for example, the sentence John is Anne's son. In this article, a simple and natural extension of LO is suggested to encompass many-argument predication. The system thus obtained corresponds to polyadic second-order logic.